2023
DOI: 10.1002/cam4.6320
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative waiting time in Stage IIIII gastric or gastroesophageal junction cancer: A population‐based cohort study

Abstract: BackgroundGastrectomy remains the curative option in gastric cancer. However, the growing concern that preoperative waiting jeopardizes survival has not been fully addressed. The present population‐based cohort study aimed to clarify the impact of preoperative waiting time (PreWT).MethodsWe included patients with clinical Stage II–III gastric cancer who received curative surgery from 2008 to 2017 of Taiwan Cancer Registry. PreWT was defined as the time from endoscopic diagnosis to surgery. The prognostic impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, previous reports indicate prolonged waiting times from diagnosis to surgery and delays in the initiation of chemotherapy due to the pandemic, and our study did not include an evaluation of these aspects [42]. However, various studies have shown that the wait time between diagnosis and treatment does not affect the prognosis of GC [43][44][45][46]. Although there are concerns about changes in the quality of treatment due to the COVID-19 pandemic, reports in Japan have shown no changes in the postoperative 30-or 90-day mortality rates or in the incidence of postoperative complications such as pneumonia and sepsis [19,47].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, previous reports indicate prolonged waiting times from diagnosis to surgery and delays in the initiation of chemotherapy due to the pandemic, and our study did not include an evaluation of these aspects [42]. However, various studies have shown that the wait time between diagnosis and treatment does not affect the prognosis of GC [43][44][45][46]. Although there are concerns about changes in the quality of treatment due to the COVID-19 pandemic, reports in Japan have shown no changes in the postoperative 30-or 90-day mortality rates or in the incidence of postoperative complications such as pneumonia and sepsis [19,47].…”
Section: Discussionmentioning
confidence: 94%
“…In pancreatic cancer, median waiting time was reported at 31 days but may extend beyond 56 days. Fortunately, waiting times alone do not appear to have a significant effect on survival for pancreatic [106], colorectal [107], gastric [108], and lung cancers [109].…”
Section: What Is the Suggested Effective Duration Of A Prehabilitatio...mentioning
confidence: 99%